Reported Sports Participation, Race, Sex, Ethnicity, and Obesity in US Adolescents From NHANES Physical Activity (PAQ_D) - Robert W. Turner PhD; Eliana M. Perrin MD, MPH; Tamera Coyne-Beasley MD, PhD; Camilla J. Peterson MPH; Asheley C. Skinner PhD (SAGE Publishing, 2015)
Objective . To understand the relationships between participation in different types of leisure time sport activity and adolescent obesity, and how those relationships might differ based on race, gender, and household income. Methods . Data consisted of 6667 students that took part in the 1999 to 2006 National Health and Nutrition Examination Survey. The authors used adjusted Wald tests to examine differences in the prevalence of obesity (body mass index >95th percentile for age and sex) by sport for boys and girls separately. Results . Among adolescent youth age 12 to 19 years, 16.6% of male leisure time sport participants and 15.3% of female sport participants were obese, compared with 23.6% for male nonathlete participant-in-other-activities and 17.0% obesity rate for female nonathlete/participant-in-other-activities. For both males and females, reported participation in leisure time sports decreased between middle school and high school, and this reduction was associated with higher body mass index.